Effect of Feed Form and Water Addition on Growth Performance of Finishing Broilers in a Hot Humid Environment - Smalling, S.; Diarra, S.S.; Amosa, F. (Pakistan Journal of Nutrition, 2019)
Background and Objective: High temperature and humidity are major challenges to poultry production in tropical countries. Several feeding strategies have been found to alleviate the effect of heat stress (HS) in poultry. This study aimed to ascertain the effects of feed physical form and water addition on the performance of finishing broilers in a hot humid environment. Materials ans Methods: A total of 180, three-week old, Cobb 500 broilers (1,207.8±22.09 g) were used for a 3-week study. Two forms of feed (whole pellet and ground pellet) were fed with 3 water: feed ratios (0; control, 0.15 and 0.3) to 3 replicates of 10 birds each in a completely randomized design. Results: Results showed lower feed intake and better feed conversion ratio on whole pellet compared to ground pellet (p<0.05). Water addition and feed form had no effects on the relative weights of carcass, breast, thighs, drumsticks, organs (liver, crop, proventriculus, small intestine, caeca, gizzard and pancreas) and digesta content of gut segments (p>0.05). There were no interaction effects of feed form and water addition on growth parameters and the relative weights of carcass, organ and digesta in the gut segments. Conclusion: Feeding pellet is beneficial in term of feed utilization but wet feeding has no effects. Further studies on higher feed: water ratios and environmental temperatures are recommended.